2020
DOI: 10.1002/slct.202002610
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Characterization of Cu3(MoO4)2(OH)2 Nanorods for High Performance Supercapacitor Electrode Application

Abstract: In the present study, Cu3(MoO4)2(OH)2 electrode materials were prepared by CTAB assisted hydrothermal method. Thermal, crystalline and bonding properties of freshly prepared samples were confirmed by thermo gravimetric analysis (TGA), x‐ray diffraction analysis (XRD), Fourier transform infrared spectroscopy (FTIR) and Raman analyses. The surface morphological features of Cu3(MoO4)2(OH)2 electrode materials were observed via Scanning electron microscopy (SEM) analysis. The concentration of cetyl trimethyl ammon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…It can be found that there are eight obvious Raman vibration bands at 289, 304, 342, 363, 405, 797, 841 and 930 cm À 1 , which is consistent with the location of vibration bands reported in the literatures. [36,37] The band at 289 cm À 1 mainly related to the lattice vibration modes and CuÀ O interactions. The vibration bands at 304, 342, 363 and 405 cm À 1 are caused by symmetrical and asymmetric bending vibrations of OÀ Mo-O within the MoO 4 tetrahedral.…”
Section: Characterization Of the Prepared Monoclinic Cu 3 (Moo 4 ) 2 ...mentioning
confidence: 99%
See 2 more Smart Citations
“…It can be found that there are eight obvious Raman vibration bands at 289, 304, 342, 363, 405, 797, 841 and 930 cm À 1 , which is consistent with the location of vibration bands reported in the literatures. [36,37] The band at 289 cm À 1 mainly related to the lattice vibration modes and CuÀ O interactions. The vibration bands at 304, 342, 363 and 405 cm À 1 are caused by symmetrical and asymmetric bending vibrations of OÀ Mo-O within the MoO 4 tetrahedral.…”
Section: Characterization Of the Prepared Monoclinic Cu 3 (Moo 4 ) 2 ...mentioning
confidence: 99%
“…The vibration bands at 797 and 841 cm À 1 corresponds to the symmetry and asymmetric stretching vibration of MoÀ O within the MoO 4 tetrahedral, respectively. [36] And the vibration peak at 930 cm À 1 corresponds to the Mo=O symmetrical tensile vibration mode. [37] Figure S3b shows the FTIR spectrum of the sample monoclinic Cu 3 (MoO 4 ) 2 (OH) 2 nanosheets.…”
Section: Characterization Of the Prepared Monoclinic Cu 3 (Moo 4 ) 2 ...mentioning
confidence: 99%
See 1 more Smart Citation